Nomenclatural notes on type materials of fourteen names in Lythraceae - Prasanth, Arun; Sardesai, Milind M. (Phytotaxa, 2024)
In the present study, we designate lectotypes and epitypes for fourteen names (for accepted names/basionyms/synonyms) of three genera Ammannia, Lagerstroemia, and Rotala of family Lythraceae, to facilitate the correct application of these names. Lectotypes are designated for three names in Ammannia, three names in Rotala, and four names in Lagerstroemia. Second-step lectotype are designated for two names in Rotala and one name in each Ammannia and Lagerstroemia. Further, an epitype for the name Rotala floribunda is assigned.